Quantification and comparison of avoidable mortality – causal relations and modification of concepts - Soltes, Michal; Gavurova, Beata (Technological and Economic Development of Economy, 2015)
The fundamental criticism of the analyses of relations between the allocated sources into healthcare system and general indicators of health status (represented by mortality) form a concept of avoidable mortality. The concept is a result of a reaction of many specialists in this field. The efficient concept of avoidable mortality that consists of treatable and preventable mortality components should provide prominent information that is not directly absorbed in the metrics of general mortality rate traditionally used for measuring the healthcare systems’ outputs. Permanent evaluation of the concept is based on confrontation of actual and relevant facts and supported by significant evidence from analytical outputs. This evaluation may help to form an efficient tool for measuring the amenable mortality with system connections as within health care system so in social policy, long-term health care policy, etc. The aim of this article is an analysis and evaluation of avoidable mortality development at conceptual and evaluative level and a specification of advantages and limitations that result from this concept. The analyses’ outputs represent a valuable platform for revision of strategic framework of the Slovak healthcare as well as for formation of targeted policies that focus on increase of healthcare system efficiency.